ERRORS AND TECHNIQUES OF THEIR CORRECTION IN THE FOREIGN LANGUAGE TEACHING - Kovalenko, A.V.; Kudritskaya, M.I. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2017)
This article discusses notions of «error» and «mistake», their importance in the foreign language teaching and main types of errors. The focus of the article is on the techniques of error correction of English learning students’ speaking writing in the classroom. How teachers deal with errors has a significant impact on the students' performance and desire for participation. Traditionally, teachers correct all the errors made by students. However, recent trends of language teaching advocate that teachers need not correct all the errors right after they are made
Keywords: error; mistake; types of errors; correction techniques; foreign language teaching